(untitled) (Clinics, 2012)
OBJECTIVE: To identify the scope and the characteristics of fall-related traumas in urgent care centers in Sergipe, Brazil and to verify potential associations among the following variables: gender, age, and where the event occurred. METHOD: This descriptive, cross-sectional study with a quantitative approach was conducted in the urgent care centers of two public referral hospitals in the state of Sergipe, Brazil. The data collection was conducted in November 2010, after approval was obtained from the Human Research Ethics Committee, through a structured interview with a sample of 509 fall victims. RESULTS: Most of the participants were male, between 0 and 19 years old, single, with no impairments or preexisting diseases, nor regular use of medication or alcohol. The victims were brought to the hospital by ambulance and were accompanied. Most events occurred at home, were same-level falls, and most frequently resulted from slipping and tripping during recreational activities with a subsequent fracture, contusion or sprain. Most victims were discharged from the hospital after care delivery. Statistically significant associations were found between place of fall and age and gender. CONCLUSION: There is a high incidence of seeking out care in urgent care centers due to falls, which constitutes a severe public health problem that affects both genders in different age groups. The adoption of preventive measures aimed to reduce such events is urgently required.